1999
DOI: 10.1016/s0261-5177(99)00023-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the touristic image of Jordan

Abstract: Abstract:Destination image has received significant attention in recent Western travel literature. However, developing and lesser-developed countries have less research attention devoted to them despite the fact image is a key factor in determining travel decisions. This study explored current visitor images of a Middle Eastern country, Jordan. On-site interviews with tourists indicated a fairly positive image of Jordan, with improvements possible in service related areas. Marketing and research implications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 27 publications
(10 reference statements)
1
28
0
1
Order By: Relevance
“…Yet competitiveness may be difficult to achieve and maintain, as has been evident in some developing countries such as in Eastern Europe (Davidson 1992, Hall 1999, sub-Saharan Africa (Brown, 1998), Jordan (Schneider & Sonmez 1999, Hazbun 2000, Ethiopia (Shanka & Frost, 1999) Described as tourism's holy grail , the destination competitiveness research stream surprisingly only commenced during the 1990s. Recent literature reviews (see Mazanec, Wober & Zins 2007, Pike 2008 concluded there was no widely accepted causal model of destination competitiveness.…”
Section: Sustained Destination Competitivenessmentioning
confidence: 99%
“…Yet competitiveness may be difficult to achieve and maintain, as has been evident in some developing countries such as in Eastern Europe (Davidson 1992, Hall 1999, sub-Saharan Africa (Brown, 1998), Jordan (Schneider & Sonmez 1999, Hazbun 2000, Ethiopia (Shanka & Frost, 1999) Described as tourism's holy grail , the destination competitiveness research stream surprisingly only commenced during the 1990s. Recent literature reviews (see Mazanec, Wober & Zins 2007, Pike 2008 concluded there was no widely accepted causal model of destination competitiveness.…”
Section: Sustained Destination Competitivenessmentioning
confidence: 99%
“…Because various authors (e.g. Crompton, 1979;Schneider and Sonmez, 1999) suggest that satisfaction is 'destination-determined' and formed by experiences, it is critically important to investigate cruise passengers' satisfaction levels in various destination attributes. Table 4 presents the results in relation to the responses to the 26 satisfaction statements.…”
Section: Onshore Satisfactionmentioning
confidence: 99%
“…The findings revealed that the visitors had a positive image about Jordan with a high rating to the dimensions of safety, hospitality, and the diversity in tourism sites. However, the sample was more neutral in their views toward tourism services asserting the lack of tourism services (Schneider, 1999). The researcher highlighted the need for enhancing and developing the tourism services.…”
Section: Literature Reviewmentioning
confidence: 93%
“…To date, only three studies have been found that investigated the image of Jordan as perceived by international tourists (Schneider & Sönmez, 1999;Alshourah, 2001;Harahsheh, 2009). Schneider and Sönmez (1999) have studied the image of Jordan as perceived by Jerash's festival visitors. The findings revealed that the visitors had a positive image about Jordan with a high rating to the dimensions of safety, hospitality, and the diversity in tourism sites.…”
Section: Literature Reviewmentioning
confidence: 99%